COVID-19 AND THE PREVALENCE OF GASTROINTESTINAL MANIFESTATIONS IN PATIENTS OF A HOSPITAL IN ANÁPOLIS, GOIÁS - Silva, Geovanna de Oliveira Araújo; de Souza, Laàsla Maria; Graciano , Maria Vità³ria Vieira; de Deus, Ana Luiza Caetano; Mendonà§a, Vinicius Oliveira; de Oliveira, Danubio Antonio (CIPEEX, 2022)
CORONAVIRUS DISEASE (COVID-19) IS A NEWLY EMERGING RESPIRATORY INFECTION CAUSED BY SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS 2 (SARS-COV-2) THAT AFFECTS THE DIGESTIVE TRACT, DESPITE MAINLY AFFECTING THE RESPIRATORY TRACT. THE OBJECTIVE OF THIS RESEARCH IS TO IDENTIFY THE PREVALENCE OF GASTROINTESTINAL CLINICAL MANIFESTATIONS IN PATIENTS WITH COVID-19 IN A HOSPITAL IN ANÁPOLIS, GOIS, BRAZIL, IN 2021. THIS IS A SINGLE-CENTER, RETROSPECTIVE, OBSERVATIONAL COHORT STUDY, WITH DATA COLLECTION FROM MEDICAL RECORDS, CARRIED OUT AT HOSPITAL EVANGLICO GOIANO, IN ANÁPOLIS, GOIS, BRAZIL, EVALUATING HOSPITALIZED PATIENTS WITH COVID-19 BETWEEN JANUARY 1, 2021 AND DECEMBER 31, 2021. DATA COLLECTION WAS CARRIED OUT WITH 153 MEDICAL RECORDS AND NO RECORD WAS DISCARDED BY CRITERIA OF EXCLUSION. IT WAS OBSERVED THAT MOST PATIENTS WERE BETWEEN 40 AND 59 YEARS OLD (41.8%), WERE MALE (50.3%) AND HAD PREVIOUS COMORBIDITY, THE MOST COMMON BEING SYSTEMIC ARTERIAL HYPERTENSION (41.1%). A HIGH PREVALENCE OF GASTROINTESTINAL SYMPTOMS (66%) WAS FOUND. THE MOST COMMON SYMPTOMS WERE: LACK OF APPETITE (22.9%), NAUSEA (7.8%) AND DIARRHEA (6.5%), AT ADMISSION; AND CONSTIPATION (31.4%), LACK OF APPETITE (18.9%) AND DIARRHEA (8.5%), DURING THE COURSE OF HOSPITALIZATION. MORE STUDIES ARE NECESSARY TO HIGHLIGHT THE IMPORTANCE OF GASTROINTESTINAL SYMPTOMS IN PATIENTS WITH COVID-19, UNDERSTAND THEIR MECHANISMS AND IDENTIFY LONG-TERM GASTROINTESTINAL CONSEQUENCES.